HUBUNGAN ANTARA SELF EFFICACY DENGAN QUALITY OF LIFE PADA PASIEN DIABETES MELLITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS KEBONSARI SURABAYA - Mawarda Hatmanti, Nety (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2017)
Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Diabetes Mellitus type 2 is a significant problem in the global health. This research was purposed to find out the correlation between self-efficacy and quality of life of the patients with Diabetes Mellitus type 2. The design of this research was cross sectional, in which 16 patients visiting the polyclinic of Puskesmas Gayungan Surabaya were chosen as the samples. The result of research using Spearman rho test showed that there was a significant correlation between self-efficacy and quality of life proved by the p value = 0.016 < 0.05. The conclusion of this research found a positive intermediate correlation between selfefficacy and quality of life so that nurses are required to ask the family to increase the patients’ self-efficacy.